Between East and West. State borders, travel documents, border crossing in Hungary and in Czechoslovakia (1946-1989) (Academic Journal of Internal Affairs, 2020)
In the publication series of the Institute of Historical Sciences of the Research Centre for Liberal Arts at the Hungarian Academy of Sciences was a book of Péter Bencsik, meeting also questions of border policing, published in 2019. The book with a uniform appearance and with simple but alluring (if we can use this attributive in case of a book) appearance is well matching to the series. The same pleasant greyish cover, the demanding hardcover protection and the inevitable three small pictures make it attractive and desirable for collectors. The title of the book is accurate. For the colleagues in law enforcement are captivating at first sight the interesting (though black and white) small photos on the cover showing characteristic scenes about border checks at the former Hungarian-Czechoslovakian border.
Keywords: border crossing; travel documents; Hungary